Parental Trigger Laws and the Power of Framing in Educational Politics - Feuerstein, Abe (Education Policy Analysis Archives, 2015)
This paper examines the discursive strategies employed by advocates of Parent Trigger laws in the United States which allow parents of children in “failing” schools, in some states, to call for interventions in the operation of the schools via petition. The paper reviews the genesis of Parent Trigger laws, the network of conservative political organizations supporting Parent Trigger legislation, and the ways in which Parent Trigger advocates have promoted the concept through the deployment of both material and symbolic resources. The paper argues that Parent Trigger laws promote a “thin” form of democratic participation that equates democracy with consumer choice through the strategic representation of public schools as broken institutions and parent trigger laws as empowering parents to choose. Support for this position is developed through an empirical qualitative analysis of a sample of media texts produced by various organizations within the Parent Trigger policy network including the American Legislative Exchange Council (ALEC), American Enterprise Institute, Heartland Institute, Parent Revolution, and others. By identifying frequently used framing devices such as metaphors, exemplars, catch-phrases, and depictions as well as reasoning devices such as root causes, consequences, and appeals to principle, the study reveals the dominant frames employed by Parent Trigger advocates and contributes to the development of a more critical perspective concerning the media produced by various interest groups.